2017
DOI: 10.1007/s00586-017-4981-2
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast in the ligamentum flavum hypertrophic activity

Abstract: We conclude that the transition of fibroblast to myofibroblasts via TGF-β pathway is a key linker between inflammation and fibrosis in LFH mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…These results indicate that TGF‐β1 stimulated the fibroblast to myofibroblast transition, and ultimately promoted fibrosis by over‐producing the ECM components listed above. These results are consistent with our previous study.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…These results indicate that TGF‐β1 stimulated the fibroblast to myofibroblast transition, and ultimately promoted fibrosis by over‐producing the ECM components listed above. These results are consistent with our previous study.…”
Section: Resultssupporting
confidence: 94%
“…The transition of fibroblasts to myofibroblasts is found in many cell types, and it is especially well documented in the field of cardiology as a key pathway leading to cardiac failure via myocardial hypertrophy and fibrosis . Hur et al for the first time, introduced the concept of fibrosis/hypertrophy pathomechanism into the field of LF and proposed that the myofibroblast transition induced by TGF‐β1 might be a key link between inflammation and LFH. The study showed the presence of myofibroblasts, which have contractile and ECM secretory functions, in the LF of LSCS patients by detecting αSMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that when suffering from increased mechanical stress, the ligamentum flavum is constantly damaged, causing a local release of inflammationrelated factors, such as TNF-α, TGF-b1, IL-1 and IL-6, which can stimulate LF fibrosis and contribute to the pathological process of HLF [12,[33][34][35][36]. Although inflammatory factors are believed to play a crucial role in HLF [5,11,[37][38][39][40], the molecular basis for LF tissue fibrosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%